Effects of Planter Type and Seeding Rate in No-tillage Systems on Wheat Yield in Pol- e Dokhtar (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
In the cropping year 2013-2014, a split plot experiment using the randomized complete block design with three replications was conducted in a field in Pol-e Dokhtar in Lorestan Province to study the effects of planter type and seeding rates used in direct and customary planting practices. Results showed there were significant differences between planters with respect to percentage of broken seeds at the 1% level. Comparison of the means indicated the highest percentage of broken seeds (5.1%) belonged to the Barzagar-e Hamadani planter and the lowest to the Gaspardo and Sfoggia direct planters. Type of planter also influenced precision in longitudinal distance at the 5% level. Moreover, comparison of the means revealed that the best uniformity in appropriate longitudinal distance between seeds in planted rows was that of the Gaspardo and Sfoggia direct planters and the worst that of the Barzegar-e Hamadani planter and that the effects of various planters were significant at the 5% level. The Gaspardo and Sfoggia direct planters, with 88.26 and 86.49%, respectively, had the maximum uniformity in depth of planting, and the Barzegar-e Hamadani with 79.03% the minimum. ANOVA suggested the various planters were not significantly different in wheat yield, while the effects of seeding rate treatments on wheat seed yield were significant at the 5% level. Nevertheless, comparison of the means showed that the Gaspardo direct planter raised seed yield by 1.32 and 11.13% compared to the Sfoggia direct planter and the Barzegar-e Hamadani planter, respectively, and that it enjoyed relative superiority over them. Moreover, comparison of the means related to seeding rates indicated the 200 kg/ha rate increased seed yield by 11.05 and 24.36%, respectively, compared to the 160 and 240 kg/ha rates. Results of this research suggested direct planting with the Gaspardo planter at the seeding rate of 200 kg/ha achieved maximum seed yield. Therefore, this combination was recommended for the region.